Estudo da influência do lítio na síntese de titanato de sódio como uma alternativa para baterias de estado sólido - Souza, Handerson Cunha de (Brasil, 2025)
The growing demand for new energy sources has been a stimulus for extensive research in the area of materials, especially in high-performance solid-state batteries. Recently, sodium trititanate (Na2Ti3O7), an inorganic chemical compound, has received attention due to its effectiveness in ion exchange and catalytic properties. However, its application as an electrolyte in solid-state batteries is limited due to its low electrical conductivity. To overcome this limitation, lithium-doped Na2Ti3O7 nanoparticles were synthesized in different proportions, ranging from 0% to 5% by mass, using the microwave-assisted hydrothermal method. Samples were extensively characterized by XRD, 0%, 1% and 5% samples were also analyzed by DTA, Raman spectroscopy and complex impedance spectroscopy. Notably, the 5% lithium doped sample exhibited an electrical resistance approximately one order of magnitude lower than the undoped material. These promising results highlight the potential of doped sodium titanate as a viable component for high-performance solidstate batteries due to its enhanced structural and conductive properties.